Implementation of Arabic Learning Through Micro Teaching Program at Babussalam Islamic Boarding School Langkat - Syamsu Nahar; Zulheddi Zulheddi; Syam’s Ismail Ghifar (Budapest International Research and Critics University, 2022)
This research is aim to examine and analyze the implementation or application of Arabic learning using the Micro Teaching program at the Babussalam Islamic Boarding School Langkat which relies on (1) Arabic learning planning, (2) implementation, (3) evaluation, and (4) inhibiting and supporting factors for learning strategy Arabic through Micro Teaching. This study uses a qualitative method. Data collection techniques used are interviews, documentation, and observation. Through this research, the following results were obtained: 1) Planning of learning strategies used by class VI students in tadris amaliyah (Micro Teaching), namely; a) Maharatul Muha>datsah, b) Maharatul Assima'ah, c) Maharatul Kitabah, d) Maharatul Qiroah. 2) Implementation of learning strategies used in traditional amaliyah (Micro Teaching) through; a) muhadasah, b) muthola'ah, c) direct learning process, d) using learning tools, e) using lecture and discussion methods, f) writing learning process. 3) Evaluation of the implementation of learning strategies in traditional amaliyah is carried out through assessments including; a) Assessment of oral and written tests, b) Assessment of performance, c) Assessment of portfolios, d) Assessment of projects, e) Assessment of attitudes, f) Assessment of instrument analysis, g) Assessment of evaluation. 4) Factors supporting the learning strategy are: a) Innovative, educative, and effective human resources, b) The majority of amaliyatu at-tadris supervisors are alumni of Islamic boarding schools, c) Adequate learning facilities, d) Adequate learning media and e) Presence of teachers - Arabic teacher. While the inhibiting factors are a small number of Indonesian-speaking teachers, teaching general subjects, not graduating from Islamic boarding schools, and aliyah students who do not know the meaning of Arabic.